Odpowiedź :
Odpowiedź:
a) 6 (2x –3 –10y)
12x - 18 -60y
b) ( 7a –3) ( 8 –2a )
56a - 14a -24 +6a
48a - 24
c) 5 ( 2x2–3x) ( -2x –x2) ( x –5 )
10x²- 15x (-2x -x²) ( x - 5)
10x² - 15x -2x² + 10x -x³ -5x²
z3x² -5x - x³
Cześć!
Szczegółowe wyjaśnienie:
a)
[tex]6(2x-3-10y)=6\cdot2x-6\cdot3-6\cdot10y=\\12x-18-60y[/tex]
b)
[tex](7a-3)(8-2a)=7a\cdot8-7a\cdot2a-3\cdot8-3\cdot(-2a)=\\56a-14a^{2} -24+6a=\\62a-14a^{2} -24=\\-14a^{2} +62a-24[/tex]
c)
[tex]5(2x^{2} -3x)(-2x-x^{2} )(x-5)=\\(10x^{2} -15x)(-2x-x^{2} )(x-5)=\\(-20x^{3} -10x^{4} +30x^{2}+15x^{3} )(x-5)=\\-5x^{3} -10x^{4} +30x^{2} )(x-5)=\\-5x^{4} +25x^{3} -10x^{5} +50x^{4} +30x^{3} -150x^{2} =\\45x^{4} +55x^{3} -10x^{5} -150x^{2} =\\-10x^{5} +45x^{4} +55x^{3} -150x^{2}[/tex]